2021
DOI: 10.26555/ijain.v7i2.317
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer medical images classification using hybrid CNN-SVM

Abstract: Lung cancer is one of the leading causes of death worldwide. Early detection of this disease increases the chances of survival. Computer-Aided Detection (CAD) has been used to process CT images of the lung to determine whether an image has traces of cancer. This paper presents an image classification method based on the hybrid Convolutional Neural Network (CNN) algorithm and Support Vector Machine (SVM). This algorithm is capable of automatically classifying and analyzing each lung image to check if there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Agarwal et al [10] proposed a method to classify lung cancers as either malignant or benign by combining a CNN with the AlexNet network model whereas Ardimento et al [17] suggested a novel ensemble-based method for classifying lung cancer more accurately using CT scan images. Saleh et al [20] developed an approach for classifying CT images of the lung using a hybrid of CNN and SVM algorithms. The goal was to effectively detect the presence of cancer cells.…”
Section: Related Workmentioning
confidence: 99%
“…Agarwal et al [10] proposed a method to classify lung cancers as either malignant or benign by combining a CNN with the AlexNet network model whereas Ardimento et al [17] suggested a novel ensemble-based method for classifying lung cancer more accurately using CT scan images. Saleh et al [20] developed an approach for classifying CT images of the lung using a hybrid of CNN and SVM algorithms. The goal was to effectively detect the presence of cancer cells.…”
Section: Related Workmentioning
confidence: 99%
“…In most cases of classification and detection, convolutional neural network shows significant performance. Recently, CNN classification of lung cancer based on computer tomography (CT) image has been reported in [17]- [20]. Study by Saleh [17], combined CNN-SVM in CT image-based lung cancer detection and succeeded in generating 97.91% accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CNN classification of lung cancer based on computer tomography (CT) image has been reported in [17]- [20]. Study by Saleh [17], combined CNN-SVM in CT image-based lung cancer detection and succeeded in generating 97.91% accuracy. Meanwhile, similar classification cases have been reported in [18], [19], generate 93.54% and 100% accuracy respectively.…”
Section: Introductionmentioning
confidence: 99%
“…6, December 2022: 6675-6683 6676 more efficient method of identifying plant diseases [8], [9]. Deep learning architecture, namely convolutional neural network (CNN), has shown remarkable performance in image classification [10]- [12]. The CNN model was used to diagnose diseases on tomato leaves in the most recent research, which yielded an accuracy score of 95% with a batch size of 16 and a total loss of 0.1265 utilizing only 4,671 images of tomato leaves.…”
Section: Introductionmentioning
confidence: 99%